Development and application of an enzyme linked immunosorbent assay for Clostridium perfringens type A enterotoxin. Issue 2 (February 1985) - Bartholomew, B A; Stringer, M F; Watson, G N; Gilbert, R J
Abstract : An enzyme linked immunosorbent assay (ELISA) has been developed to quantitate faecal Clostridium perfringens enterotoxin in the investigation of C perfringens food poisoning. The sandwich ELISA could be carried out in 24 h and was sensitive enough to detect as little as 5 ng/g of enterotoxin in faeces. Specificity of the assay was shown by comparing results with those obtained from other standard toxin assays, such as double gel diffusion and counterimmunoelectrophoresis, and by the assay of faecal material from control groups. By means of the ELISA method, 515 faecal samples from 50 separate outbreaks of C perfringens food poisoning were examined, together with 21 food samples from 12 of the outbreaks. A clear distinction was noted between faecal samples collected on the first two days of an outbreak, where 77% were enterotoxin positive, and those specimens collected later than the second day, when only 33% had detectable enterotoxin. The ELISA is recommended as a valuable tool in the investigation of C perfringens foodborne illness.